2018
DOI: 10.1007/s00429-018-1755-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of the P300 from childhood to adulthood: a multimodal EEG and MRI study

Abstract: Maturation of attentional processes is central to cognitive development. The electrophysiological P300 is associated with rapid allocation of attention, and bridges stimulus and response processing. P300 is among the most studied and robust electrophysiological components, but how different subcomponents of the P300 develop from childhood to adulthood and relate to structural properties of the cerebral cortex is not well understood. We investigated age-related differences in both early visual and P300 componen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
2
10
1
Order By: Relevance
“…If we use the interpretation that the Pe indexes error awareness and strategic adjustment (Nieuwenhuis et al, 2001;Ridderinkhof et al, 2009), while the ERN reflects automatic, motivational error processing, the differing trajectories would imply that while the ability to detect and process errors consciously reaches full maturity early, the ability to engage motivationally to respond quickly and automatically to errors has a more protracted development. Interestingly, these age-associations differ from what has been observed for the related N200 and P300 ERPs, where the N200 has generally been shown to decrease in strength with age (Downes et al, 2017), and P300 to increase (van Dinteren et al, 2014), which is also what we have observed previously in the same sample as the present study (Overbye et al, 2018).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…If we use the interpretation that the Pe indexes error awareness and strategic adjustment (Nieuwenhuis et al, 2001;Ridderinkhof et al, 2009), while the ERN reflects automatic, motivational error processing, the differing trajectories would imply that while the ability to detect and process errors consciously reaches full maturity early, the ability to engage motivationally to respond quickly and automatically to errors has a more protracted development. Interestingly, these age-associations differ from what has been observed for the related N200 and P300 ERPs, where the N200 has generally been shown to decrease in strength with age (Downes et al, 2017), and P300 to increase (van Dinteren et al, 2014), which is also what we have observed previously in the same sample as the present study (Overbye et al, 2018).…”
Section: Discussioncontrasting
confidence: 87%
“…In youth, we recently found a positive relationship between P300 strength and cortical surface area in a region in the left inferior temporal gyrus (Overbye et al, 2018), but no previous studies have tested the associations between ERN or Pe and brain structure. We did, however, not find any significant associations between either ERN or Pe and regional cingulate cortex thickness or surface area in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An extensive review and meta-analysis of developmental studies on the P300 in auditory oddball tasks by van Dinteren, Arns, Jongsma, and Kessels (2014b) concluded that the P300 amplitude increases from childhood to adulthood. This is also what we recently found for a visual oddball task (Overbye, Huster, Walhovd, Fjell, & Tamnes, 2018).…”
Section: Interference Control Is Commonly Measured With Behavioral Tasupporting
confidence: 91%
“…Moreover, WT/MEAN pair yields greater R value than Hilbert/MEAN over parietal region (LP) as well and the difference is significant. According to other researches, activity over parietal region is essentially elicited by P300 response which is a significant oddball event [97,98]. Thus, we believe that WT/PCA and WT/MEAN pairs provide good performance for PLV to localize the connectivity triggered by P300 response.…”
Section: Resultsmentioning
confidence: 68%